The advantages of mass normalized electrochemical impedance spectra for the determination of the kinetic parameters of LiMn2O4 cathodes - Kamenskii, M.A.; Eliseeva, S.N.; Tolstopjatova, E.G.; Volkov, A.I.; Zhuzhelskii, D.V.; Kondratiev, V.V. (Electrochimica acta, 2019)
The electrochemical properties of LiMn2O4 (LMO) based cathode material with conducting polymer binder containing poly-3,4-ethylenedioxythiophene/polystyrene sulfonate (PEDOT:PSS) dispersion and carboxymethylcellulose (СМС) were investigated for electrodes of three different thicknesses. The effect of the thickness of LMO cathode layer on the kinetic parameters of electrode processes (Rct, Dapp, i0) derived from electrochemical impedance spectroscopy (EIS) has been experimentally analyzed. A simple approach for estimating the possible influence of various real surface areas of electrodes with different active masses by plotting the dependencies normalized to the mass of the active component was proposed. This approach assumes that the real active surface area is defined as the total surface of all particles of the active component, and their mass is proportional to the area given that size of active grains is subject to random statistical distribution. It leads to determination of more reliable values of kinetic parameters and gives the base for more reasonable comparison of results of different works, as was illustrated in the example of LMO. It has been shown that the large difference in the values of charge transfer resistance Rct and apparent diffusion coefficients Dapp for electrodes with various thicknesses becomes insignificant after EIS data normalization to mass loading. While the values obtained from as-recorded non-normalized EIS data referred to the visible area of electrode differ considerably, the normalization of EIS spectra to LMO mass and calculation referred to the real surface area estimated from Brunauer-Emmet-Teller (BET) yields closer values. •Effect of LMO electrode thickness on the EIS spectra has been experimentally analyzed.•Alternative approach of analysis of EIS spectra was proposed.•Influence of various real surface areas of LMO electrodes on EIS spectra was shown.•Mass-normalized EIS spectra give similar values of surface-related kinetic parameters.